1999
DOI: 10.1074/jbc.274.52.37012
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of α-Actinin in Activated Platelets

Abstract: The integrin ␣ IIb ␤ 3 mediates tyrosine phosphorylation of a 105-kDa protein (pp105) in activated platelets. We have partially purified a 105-kDa tyrosine-phosphorylated protein from platelets stimulated with phorbol 12-myristate 13-acetate and obtained the sequence of an internal 12-mer peptide derived from this protein. The sequence was identical to human ␣-actinin sequences deposited in the Swiss Protein Database. ␣-Actinin, a 105-kDa protein in platelets, was subsequently purified from activated platelets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 59 publications
4
39
1
Order By: Relevance
“…This regulation of the myosin heavy chain differs from the usual regulation through the light chain ( Conti and Adelstein, 2008 ). Talin, ␣ -actinin, and the actin nucleator mDia1 also appeared regulated (to a lesser extent), and all have been implicated previously in phagocytosis (respectively: [( Turner et al, 1989 ;Greenberg et al, 1990 ); ( Crowley and Horwitz, 1995 ;Izaguirre et al, 1999 ); ( Meng et al, 2004 ;Brandt et al, 2007 )]). Although phospho-paxillin was downregulated in our imaging studies, it was not prominent in our immunoblots and was unaffected by blebbistatin, which otherwise mimicked CD47 ' s inhibitory effects ( Figs.…”
Section: Phosphotyrosine Activation Of Nmm Iia In Phagocytosismentioning
confidence: 97%
See 1 more Smart Citation
“…This regulation of the myosin heavy chain differs from the usual regulation through the light chain ( Conti and Adelstein, 2008 ). Talin, ␣ -actinin, and the actin nucleator mDia1 also appeared regulated (to a lesser extent), and all have been implicated previously in phagocytosis (respectively: [( Turner et al, 1989 ;Greenberg et al, 1990 ); ( Crowley and Horwitz, 1995 ;Izaguirre et al, 1999 ); ( Meng et al, 2004 ;Brandt et al, 2007 )]). Although phospho-paxillin was downregulated in our imaging studies, it was not prominent in our immunoblots and was unaffected by blebbistatin, which otherwise mimicked CD47 ' s inhibitory effects ( Figs.…”
Section: Phosphotyrosine Activation Of Nmm Iia In Phagocytosismentioning
confidence: 97%
“…8 C , bottom). Additional cytoskeletal proteins that were detected in the macrophages and might be targeted in the CD47-SIRP ␣ phosphotyrosine pathway include Talin-1 ( Turner et al, 1989 ;Greenberg et al, 1990 ), mDIA1 ( Meng et al, 2004 ), and ␣ -actinin ( Crowley and Horwitz, 1995 ;Izaguirre et al, 1999 ). Capabilities of MS to identify phosphotyrosine are currently limited, as here, by low sequence coverage and sub-stoichiometric phosphorylation ( McLachlin and Chait, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…COS-7 cells were transiently transfected with pCDNA3 vector, HA-ACTN4 wt, or HA-ACTN4 mutant. The actin cytoskeleton was pelleted from cell lysates at 10 5 ϫ g (23) and the amount of HA-␣-actinin-4 assessed by Western blot as analyzed with a polyclonal anti-HA tag antibody (1:1000). As shown in Figure 2b, compared to the wt form, a significantly greater proportion of mutant murine ␣-actinin-4 associated with the insoluble cytoskeletal fraction containing an equal amount of pelleted actin.…”
Section: Cloning and Mutagenesis Of Murine Actn4 Cdnamentioning
confidence: 99%
“…We have recently reported that ␣-actinin is tyrosine-phosphorylated in activated platelets (1). Tyrosine phosphorylation of ␣-actinin was also observed in activated T-cells (31).…”
mentioning
confidence: 99%